Internalisasi Sifat Wara’ dalam Konsumsi Makanan Halal (Telaah Teori Konstruksi Sosial Peter L. Berger) - Hanifah Hertanti Putri; Aziz Muslim (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This paper will reveal the Sufistic dimensions implicit in the government's discourse in enforcing the obligation of halal certification for food products, beverages, slaughtered animals, and slaughter services in 2024. To analyze this paper, the author uses a critical discourse analysis approach by utilizing the theory of Peter L. Berger. The results of the discussion, it can be concluded that in order to create sustainability in the existence of the government discourse, it is necessary to apply three points of Berger's thinking (Externalization, Objectivity, and Internalization) in order to reveal the implied meaning in the discourse. So that the obedience of each individual is not just obeying the rules of the state but is able to absorb the philosophy behind the discourse and make it the subjective consciousness of the individual.